2012
DOI: 10.1093/molehr/gas022
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma microRNAs: potential biomarkers for spermatogenesis status

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs (18-25 nt), playing important regulatory roles via interaction with cellular messenger RNAs. The altered expression of miRNAs in specific tissues has been associated with diseases such as cancer and diabetes. We examined the presence of two selected miRNAs (miR-19b and let-7a) in human seminal plasma from fertile men and idiopathic infertile patients with oligozoospermia and non-obstructive azoospermia (NOA) using quantitative real-time PCR. We detected miRNAs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 47 publications
5
98
1
5
Order By: Relevance
“…miR-34c, which is also present in humans, mice and bull sperm (Amanai et al 2006, Krawetz et al 2011, Stowe et al 2014, was detected in all the three libraries from pig ejaculated sperm, epididymal sperm and seminal plasma, indicating that this miRNA species is highly conserved across mammals and confirming that it plays a significant biological role in spermatogenesis or in early embryonic development. We also found that three miRNAs (ssc-let-7a, ssc-miR26a and ssc-miR-10b) were shared in the top 10 most abundant miRNAs in the three libraries, and one of them (miR-let-7a) was detected in mouse epididymal sperm and human seminal plasma (Liu et al 2012a, Wu et al 2012, Cheong et al 2014) and shown to be involved in the regulation of embryo implantation in mice (Liu et al 2012a, Cheong et al 2014). Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…miR-34c, which is also present in humans, mice and bull sperm (Amanai et al 2006, Krawetz et al 2011, Stowe et al 2014, was detected in all the three libraries from pig ejaculated sperm, epididymal sperm and seminal plasma, indicating that this miRNA species is highly conserved across mammals and confirming that it plays a significant biological role in spermatogenesis or in early embryonic development. We also found that three miRNAs (ssc-let-7a, ssc-miR26a and ssc-miR-10b) were shared in the top 10 most abundant miRNAs in the three libraries, and one of them (miR-let-7a) was detected in mouse epididymal sperm and human seminal plasma (Liu et al 2012a, Wu et al 2012, Cheong et al 2014) and shown to be involved in the regulation of embryo implantation in mice (Liu et al 2012a, Cheong et al 2014). Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 73%
“…We also found that three miRNAs (ssc-let-7a, ssc-miR26a and ssc-miR-10b) were shared in the top 10 most abundant miRNAs in the three libraries, and one of them (miR-let-7a) was detected in mouse epididymal sperm and human seminal plasma (Liu et al 2012a, Wu et al 2012, Cheong et al 2014) and shown to be involved in the regulation of embryo implantation in mice (Liu et al 2012a, Cheong et al 2014). Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012). Studies have shown that both miR-26a and miR10b, which are also present in mouse and bull sperms (Amanai et al 2006, Bissonnette et al 2009), appear to be associated with carcinogenesis (Ma et al 2007, Kato et al 2015, but their role in spermatogenesis and in early embryonic development remains unknown.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, Wu and his colleagues showed that seminal plasma microRNAs can be regarded as potential biomarkers for the evaluation of spermatogenesis. The miR19b and let-7a miRNAs have shown aberrant over-expression in the seminal plasma of men with idiopathic NOA compared with fertile controls that may be an indicator of spermatogenic failure [28].…”
Section: Discussionmentioning
confidence: 99%